Public Participation in the Process of Forming Law No. 3 of 2022 concerning the National Capital - Hatta, Moh. (Nursyam Centre, 2023)
This research is normative research to answer questions about how the Pancasila legal state provides space for community participation and to what extent community participation is carried out in the process of forming Law Number 3 of 2022 concerning the State Capital. This research is normative research using a statutory approach and a conceptual approach with the method of writing descriptive analysis. The data collected is collected using text review which is then compiled and analyzed with a deductive mindset The conclusion in this study is the lack of community involvement in the formation of Law Number 3 of 2022 concerning the State Capital. This is certainly not in line with the principles and values contained in Pancasila as an ideology and philosophy of life for the nation, which opens up space for public participation in the process of forming a legal product. In line with the conclusions above, each authorized institution needs to provide a wider space so that the community can contribute to the formation of a law and regulation, besides that it is also important that the community is not apathetic in contributing to it. So on the part of state institutions and society, there is a shared principle that public involvement is very important to create a legal product that is in the interests of the people.